Grupo centrado na pessoa no contexto do Sistema Único de Saúde : experiência com mulheres que vivenciam o ciclo gravídico puerperal - Barbalho, Adriana Mendes (2023)
Pregnancy, delivery and birth, as biological, cultural, and historical events, have undergone significant transformations over time: from family and restricted of the female universe, with the necessary care provided by midwives, they have become predominantly institutionalized/hospital and medicalized care. In contrast to this scenario, the humanization movement proposes a humanistic paradigm of care for pregnancy, delivery, and birth, which is now foreseen in several Programs and Public Policies created by the Ministry of Health, which address the relevance of comprehensive care and highlight the positive experience of women in pregnancy and childbirth as essential for the implementation of humanized care models. In this sense, the study was conducted with the objective of understanding the experience of a group guided by the Person-Centered Approach with women who experience the pregnancypuerperal cycle, in the context of Primary Care of the Unified Health System. This study was developed from a qualitative methodological proposal, of phenomenological inspiration, in which the reference of the Person-Centered Approach was adopted from the following conceptual assumptions: Actualizing Tendence and facilitating attitudes, Congruence, Unconditional Positive Consideration and Empathic Comprehension, as guidelines for interventional practices for information collection and understanding. In this perspective, the collection of information was carried out through a group, proposed as a modality of psychological care experienced with pregnant and postpartum women, and four meetings were held in the months of May and June 2022. The research instruments used were the Versions of Meaning (VS’s) written by the researcher/facilitator at the end of each meeting and the phenomenological interview, conducted in a group with the participants in the last meeting and recorded in audio. To understand the group experience, the information was organized into Axes of Meaning and considered from the premises of the PCA in dialogue with studies linked to the themes emerged. The Axes elaborated from the VS’s demonstrate that aspects and trends typical of the development of the group based on the PCA were evidenced and present the description of the group as a space of reception and experiential freedom, in which the expression - by the participants - of significant experiences related to pregnancy was facilitated, childbirth and puerperium. The Axes also bring the sense that the group experience was constituted as a promoter of exchanges and mutual support, development, and meaningful learning. With regard to the Axes formulated based on the Phenomenological Interview, they reveal that the women understood the participation in the group as a positive experience, which provided care to the emotional aspects, boosting self-knowledge and development, and facilitator of constructive changes in the experience of motherhood. The study enabled the understanding of the viability of a group based on PCA in comprehensive care for women's health in the pregnancy-puerperal period, as a collaborative practice for the implementation of humanized care, evidencing the convergences between the principles of PCA and those that guide the practice in the care of the Unified Health System.